Artist blacksmithing techniques in action - Parkinson, Peter; Sheldon, Mark; Condie, John ([England, U.K.] : Crowood Films, 2007)
Artist Blacksmithing explains the fundamental techniques of working with hot iron and steel, and suggests how those techniques can be used creatively in designs
Instructor: Peter Parkinson
DVD format
Keywords: Blacksmithing -- Study and teaching; Artist-blacksmiths